Multimedia Courseware Selection Using Analytical Hierarchy Process (AHP) - Jaiballan, Mageswary (2007)
This project focuses on the application of a Multi-Criteria Decision Making (MCDM) method called Analytic Hierarchy Process (AHP) to select the best educational courseware in a group decision making environemnt. AHP, developed by Saaty (1980), is a systematic and comprehensive method widely used in decision making as it has the capability to assist decison makers in both qualitative and quantitative situations.